A process for rapid strengthening and toughening of Al-Zn-Mg-Cu alloy induced by high-density dislocations

Through the high-density dislocation induction process method, the problems of long aging time and insufficient material toughness of Al-Zn-Mg-Cu high-strength aluminum alloy are solved, and rapid toughening and improved production efficiency are achieved.

CN117448709BActive Publication Date: 2025-04-15HUBEI ENG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211241236.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-11
Publication Date
2025-04-15
Estimated Expiration
2042-10-11

AI Technical Summary

Technical Problem

The aging time of Al-Zn-Mg-Cu high-strength aluminum alloy is too long, which leads to high production costs and production rhythms. At the same time, the high strength of the material leads to reduced shaping and toughness, which is prone to brittle breakage and fatigue fracture problems.

Method used

Through high-density dislocation-induced process methods, including thermal solution-quenching treatment, pre-aging heat treatment, deformation electric shock treatment and final artificial aging heat treatment, the dislocation density of Al-Zn-Mg-Cu aluminum alloy and the formation of nano-scale precipitation phases are improved, and rapid strength and toughening are achieved.

Benefits of technology

The aging time of Al-Zn-Mg-Cu aluminum alloy is significantly shortened, and its strength and toughness are better than that of traditional T6 aging state, while improving the plasticity of the material, avoiding brittle breakage and fatigue fracture problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117448709B_ABST
    Figure CN117448709B_ABST
Patent Text Reader

Abstract

The present invention discloses a process for rapid toughening of Al-Zn-Mg-Cu alloy induced by high-density dislocations, comprising the following steps: performing hot solution-quenching treatment on Al-Zn-Mg-Cu aluminum alloy by heat treatment process; performing artificial pre-aging heat treatment on Al-Zn-Mg-Cu aluminum alloy after solution; increasing dislocation density in Al-Zn-Mg-Cu aluminum alloy by deformation electric shock treatment; the process of deformation electric shock treatment includes: intermittently applying instantaneous current shock during material deformation; performing final artificial aging heat treatment on Al-Zn-Mg-Cu aluminum alloy. The present invention accelerates the aging precipitation strengthening of Al-Zn-Mg-Cu aluminum alloy by increasing the dislocation density of Al-Zn-Mg-Cu high-strength aluminum alloy, so as to achieve the purpose of rapidly regulating the toughness of Al-Zn-Mg-Cu aluminum alloy; the method is energy-saving, environmentally friendly, and simple to operate, and the mechanical properties of the obtained material exceed those of the traditional T6 aging state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material science, and in particular relates to a process for rapidly strengthening and toughening an Al-Zn-Mg-Cu alloy by inducing high-density dislocations. Background Art

[0002] Al-Zn-Mg-Cu high-strength aluminum alloy has the advantages of high specific strength and low density, and is widely used in the aerospace field. In recent years, with the growing demand for energy conservation and emission reduction in automobiles, the use of Al-Zn-Mg-Cu high-strength aluminum alloy to replace traditional steel in automobile structural parts to achieve lightweighting of the entire vehicle has been favored. Among them, Al-Zn-Mg-Cu high-strength aluminum alloy is used in key components such as floor longitudinal beams. Despite this, the most widely used aluminum alloy in passenger cars is still the 5-series and 6-series aluminum alloys with slightly lower strength. This is mainly because the artificial aging time required for Al-Zn-Mg-Cu aluminum alloy to reach high strength is too long (T6 peak aging time is usually 24 hours), which greatly increases the production cost of enterprises and seriously affects the production rhythm of the entire vehicle. More importantly, the high strength of Al-Zn-Mg-Cu high-strength aluminum alloy mainly comes from the large amount of nanoscale second phases precipitated in its aluminum matrix (face-centered cubic structure). These precipitated phases mainly include GP zone, η' phase and η phase. While these precipitated phases increase the overall strength of the material, they damage the plasticity and toughness of the material, causing the components to be prone to brittle fracture, fatigue fracture and other problems during use.

[0003] In response to the above problems, both the academic and engineering communities have tried many improved methods. These methods mainly include the following aspects: First, improve the heat treatment aging process; for example, adopt double-stage aging, multi-stage aging, intermittent aging, paint aging, etc. Among them, the invention patent with publication number: CN113846279A provides a process method of natural aging first and then high-temperature rapid aging. This aging scheme can shorten the original 24-hour artificial aging time to 4 hours, greatly saving production time and improving production efficiency. However, this method can only make the hardness of the material equivalent to that of T6 peak aging, and may not improve the strength, plasticity and toughness of the material. Second, introduce lattice defects into Al-Zn-Mg-Cu high-strength aluminum alloy; it is well known that lattice defects (grain boundaries, dislocations, vacancies, etc.) can improve the strength of metal materials. Introducing a large number of lattice defects into the aluminum matrix can quickly strengthen Al-Zn-Mg-Cu aluminum alloy. Common processes of this type include deformation heat treatment, large plastic deformation treatment, etc., but the introduction of defects usually reduces the plasticity of the material. Third, use external energy field to assist aging treatment; the long aging time of Al-Zn-Mg-Cu high-strength aluminum alloy is mainly due to the fact that the GP zone and η' phase in the material are easily dissolved at a higher temperature (180°C), and the diffusion power of solute atoms is insufficient when the temperature is too low. Therefore, researchers have proposed a method of external energy field assisted aging, which mainly includes cyclic strain aging, electromagnetic flow assisted aging, etc. The invention patent with authorization announcement number CN103614673B provides a method of increasing pulse electricity in an aging furnace to shorten the aging time. This method shortens the artificial aging time to a certain extent, but it is obvious that the strength and toughness of the obtained material are inferior to the traditional T6 aging (120°C insulation for 24 hours). The invention patent with authorization announcement number CN109680230B provides an artificial aging process assisted by a magnetic field after electric pulse solid solution. This method shortens the aging time of the aluminum alloy to a certain extent, but the strength and toughness of the material are not significantly improved compared with T6. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a process method for rapid strengthening and toughening of Al-Zn-Mg-Cu alloy induced by high-density dislocation, by increasing the dislocation density of Al-Zn-Mg-Cu high-strength aluminum alloy, thereby accelerating the aging precipitation strengthening of the material, so as to achieve the purpose of rapidly regulating the strength and toughness of Al-Zn-Mg-Cu aluminum alloy; the method is energy-saving, environmentally friendly, and simple to operate, and the mechanical properties of the obtained material exceed those of the traditional T6 aging state.

[0005] In order to achieve the above object, the present invention adopts the following technical measures: a process for rapidly strengthening and toughening Al-Zn-Mg-Cu alloy by inducing high-density dislocation, comprising the following steps:

[0006] Step 1, using a heat treatment process to perform a hot solution-quenching treatment on the Al-Zn-Mg-Cu aluminum alloy; the temperature during the hot solution treatment is 460°C to 490°C, the insulation time is 20min to 60min, and after the insulation is completed, the material is quickly placed in water and cooled to room temperature;

[0007] Step 2, performing artificial pre-aging heat treatment on the Al-Zn-Mg-Cu aluminum alloy after solid solution; the pre-aging heat treatment is to place the material in an environment of 90°C to 130°C for 20min to 120min, and after the insulation is completed, place the material in the air for natural cooling;

[0008] Step 3, using deformation electric shock treatment to increase the dislocation density in the Al-Zn-Mg-Cu aluminum alloy;

[0009] The process of deformation electric shock treatment includes: intermittently applying instantaneous current shock during the material deformation process. The current density and power-on time of a single electric shock must meet the following relationship:

[0010]

[0011] Where: The unit of current density j is ampere per square millimeter (A / mm 2 ), the unit of power-on time t is seconds (s); the duration of each instantaneous electric shock is 0.1s to 2s, and the interval between two electric shocks is 1s to 30s; the number of electric shocks is related to the deformation of the material, usually between 2 and 50 times; the deformation treatment of the material can be rolling, stretching and forging, and its strain rate is 1×10 -3 s -1 ~5×10 -2 s -1 , the deformation is greater than 5% and does not cause instability such as cracking or shrinkage of the material; the electric shock can be in the form of AC, DC or pulse current, and the angle between the direction of the current and the direction of material deformation is less than 30°;

[0012] Step 4, performing a final artificial aging heat treatment on the Al-Zn-Mg-Cu aluminum alloy; the final artificial aging heat treatment is to place the material in an environment of 140° C. to 180° C. for 20 min to 60 min, and after the insulation is completed, place the material in the air for natural cooling.

[0013] The principle of the process method of the present invention is as follows: Step 1 of the present invention is to perform a hot solution-quenching treatment on the Al-Zn-Mg-Cu high-strength aluminum alloy. The purpose of this treatment process is to form a supersaturated solid solution of solute atoms such as Zn, Mg, and Cu in the aluminum matrix. This step is to prepare for precipitation strengthening in the subsequent material. In industry, this operation is generally completed using a resistance furnace. Step 2 of the present invention is to perform a pre-aging treatment on the Al-Zn-Mg-Cu high-strength aluminum alloy. The purpose of this treatment is to generate nano-scale precipitation phases in the aluminum matrix, mainly GP zones. Therefore, the time is not easy to be too long and the temperature is not easy to be too high. These precipitation phases can pin dislocations in the subsequent deformation process and promote dislocation proliferation, which is a prerequisite for the formation of high-density dislocations.

[0014] Step 3 of the present invention is to perform an electric shock treatment on the deformation of the Al-Zn-Mg-Cu high-strength aluminum alloy. The purpose of this treatment is to produce high-density dislocations in the aluminum matrix. Plastic deformation can generate high-density dislocations, but the dislocations generated by plastic deformation alone usually reduce the plasticity and toughness of the material. For this reason, the present invention introduces electric shock treatment during the plastic deformation process, and utilizes the principle of electroplasticity to improve the plasticity of the Al-Zn-Mg-Cu high-strength aluminum alloy after deformation. In addition, electric shock can also increase the dislocation density in the material. Therefore, it is particularly important to adopt a suitable electric shock treatment process in this treatment process.

[0015] Step 4 of the present invention is to perform the final artificial aging heat treatment on the Al-Zn-Mg-Cu high-strength aluminum alloy. The main purpose of this treatment is to quickly form a large number of nano-scale precipitation phases that play a strengthening role in the aluminum matrix, which are mainly η' phase and η phase. Due to the previous treatment, there are a large number of solute atoms and high-density dislocations in the aluminum matrix. The diffusion of solute atoms in the dislocations is mainly "tube diffusion", which is much faster than the "body diffusion" in the aluminum matrix, resulting in a significant increase in the precipitation rate of the strengthening phase. The Al-Zn-Mg-Cu high-strength aluminum alloy prepared by the above process is usually stronger than the Al-Zn-Mg-Cu high-strength aluminum alloy in the traditional T6 aging state due to the combined effect of dislocation strengthening and second phase strengthening. At the same time, due to the introduction of the "electroplastic effect" of the electric current, the plasticity and toughness of the material are also better than the traditional T6 aging state.

[0016] In summary, compared with the prior art, the present invention has the following beneficial effects: 1. The strength and toughness of the Al-Zn-Mg-Cu high-strength aluminum alloy after treatment by this process are better than those in the traditional T6 aging state; 2. The aging time of this process is shortened by about 90% compared with the traditional T6 artificial aging. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is the process roadmap for the rapid strengthening and toughening of the Al-Zn-Mg-Cu alloy induced by high-density dislocations of the present invention. DETAILED DESCRIPTION

[0018] Several specific examples are listed below to illustrate the present invention in detail, among which: Figure 1 This is the process roadmap for the rapid strengthening and toughening of the Al-Zn-Mg-Cu alloy induced by high-density dislocations of the present invention.

[0019] Example 1

[0020] The chemical element composition (mass percentage) of the Al-Zn-Mg-Cu aluminum alloy selected in this example is as follows: element Zn: 6.18%; Mg: 2.5%; Cu: 2.0%; Zr: 0.15%; Si: 0.10%; Fe<0.10%; the rest is Al. The specific process implementation steps are as follows:

[0021] Step 1: First, take a piece of Al-Zn-Mg-Cu aluminum alloy with a size of 500mm×20mm×2mm, put it into a resistance furnace that has been kept at 475℃ for 50 minutes, take the material out of the resistance furnace and quickly put it into water to cool to room temperature. The time to transfer from the resistance furnace to the water should be less than 6 seconds;

[0022] Step 2: Place the sample in step 1 in a resistance furnace that has been kept at 130°C for 90 minutes for pre-aging treatment. After the treatment, take the material out of the resistance furnace and place it in the air to cool to room temperature.

[0023] Step 3: Place the sample of step 2 on a plate rolling mill for rolling. During the rolling process, the material is electrified. The rolling process is performed in 5 passes, and the thinning amount of each pass is about 5%. The direction of the current is consistent with the rolling direction. A direct current is used, and the current density is 122A / mm 2 The duration of a single electric shock is 0.5s, the interval between two adjacent electric shocks is 5s, and the rolling speed is 10mm·s -1 , the number of electric shocks during each rolling process is 5;

[0024] Step 4: Place the material after the deformation electric shock treatment into a resistance furnace and keep it at 160°C for 35 minutes for final artificial aging heat treatment. After the treatment is completed, take the material out of the resistance furnace and place it in the air to cool to room temperature.

[0025] At this point, the material processing is completed. Samples are taken from this material for uniaxial tensile test and compared with traditional T6 aging samples. Each state of the sample is tested 5 times, and the results are shown in Table 1:

[0026] Table 1

[0027]

[0028] It can be seen from Table 1 that compared with the traditional artificial aging process, the artificial aging time of the present invention is only 1.7 hours, and the strength and plasticity of the obtained Al-Zn-Mg-Cu high-strength aluminum alloy are better than those of the traditional T6 aged aluminum alloy.

[0029] Example 2

[0030] The chemical element composition (mass percentage) of the Al-Zn-Mg-Cu aluminum alloy selected in this example is as follows: element Zn: 6.78%; Mg: 2.59%; Cu: 1.39%; Cr: 0.22%; Fe: 0.36%; Ti: 0.029%; Si < 0.10%; the rest is Al. The specific process implementation steps are as follows:

[0031] Step 1: First, take a piece of Al-Zn-Mg-Cu aluminum alloy with a size of 200mm×15mm×1.5mm, put it into a resistance furnace that has been kept at 475℃ for 50 minutes, take the material out of the resistance furnace and quickly put it into water to cool to room temperature. The time to transfer from the resistance furnace to the water should be less than 6 seconds;

[0032] Step 2: Place the sample in step 1 in a resistance furnace that has been kept at 120°C for 120 minutes for pre-aging treatment. After the treatment is completed, take the material out of the resistance furnace and place it in the air to cool to room temperature;

[0033] Step 3: Clamp the sample of step 2 onto the stretching machine for stretching. During the stretching process, an AC pulse current is passed through the material. The direction of the current is consistent with the direction of stretching. The peak current density is 160A / mm 2 The duration of a single electric shock is 0.8 s, the interval between two adjacent electric shocks is 10 s, the number of electric shocks is 8, and the material strain rate is 2×10 - 3 s -1 , stretching until the uniform elongation of the material is 10%;

[0034] Step 4: Place the material after the deformation electric shock treatment into a resistance furnace and keep it at 175°C for 30 minutes for final artificial aging heat treatment. After the treatment is completed, take the material out of the resistance furnace and place it in the air to cool to room temperature.

[0035] At this point, the material processing is completed. Samples are taken from this material for uniaxial tensile test and compared with traditional T6 aging samples. Each state of the sample is tested 5 times, and the results are shown in Table 2:

[0036] Table 2

[0037]

[0038]

[0039] It can be seen from Table 2 that compared with the traditional artificial aging process, the artificial aging time of the present invention is only 2.5 hours, and the strength and plasticity of the obtained Al-Zn-Mg-Cu high-strength aluminum alloy are better than those of the traditional T6 aged aluminum alloy.

[0040] The above is an exemplary description of the present invention. It should be noted that the above embodiments can only be used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be done by other technicians in this field without expending creative labor falls within the scope of protection of the present invention.

Claims

1. A process for rapidly strengthening and toughening Al-Zn-Mg-Cu alloy by inducing high-density dislocations, characterized in that: The following steps are involved: S1. Performing a hot solution-quenching treatment on the Al-Zn-Mg-Cu aluminum alloy by using a heat treatment process; the temperature during the hot solution treatment is 460°C to 490°C, the insulation time is 20min to 60min, and after the insulation is completed, the material is quickly placed in water and cooled to room temperature; S2. Perform artificial pre-aging heat treatment on the Al-Zn-Mg-Cu aluminum alloy after solid solution; the pre-aging heat treatment is to place the material in an environment of 90°C to 130°C for 20min to 120min, and after the insulation is completed, place the material in the air for natural cooling; S3, using deformation electric shock treatment to increase the dislocation density in Al-Zn-Mg-Cu aluminum alloy; The process of deformation electric shock treatment includes: intermittently applying instantaneous current shock during the material deformation process, and the current density and power-on time of a single electric shock satisfy the following relationship: Where: j is the current density, in amperes per square millimeter; t is the power-on time, in seconds; the duration of each instantaneous electric shock is 0.1s to 2s, and the interval between two electric shocks is 1s to 30s; the number of electric shocks is related to the deformation of the material, which is between 2 and 50 times; the deformation treatment of the material adopts rolling, stretching or forging, and its strain rate is 1×10 -3 s -1 ~5×10 -2 s -1 , the deformation is greater than 5% and does not cause cracking or shrinkage instability of the material; the electric shock uses AC, DC or pulse current, and the angle between the current direction and the material deformation direction is less than 30°; S4. Perform a final artificial aging heat treatment on the Al-Zn-Mg-Cu aluminum alloy. The final artificial aging heat treatment is to place the material in an environment of 140°C to 180°C for 20 minutes to 60 minutes, and after the insulation is completed, place the material in the air for natural cooling.

Citation Information

Patent Citations

  • A method for achieving rapid aging heat treatment of aluminum alloys

    CN103614673B

  • An electromagnetic pulse rapid solution-aging process for aluminum alloy components

    CN109680230B

  • Ultra-fast aging process for 7075 aluminum alloy and application thereof

    CN113846279A